ANALISIS PENGARUH CAR, BOPO, NPF DAN FDR TERHADAP ROA (Studi pada Bank Umum Syariah di Indonesia Periode Tahun 2016-2019) - Faizal Fachri, Muhamad; Mahfudz, Mahfudz (Faculty of Economics and Business Diponegoro University, 2021)
This study was conducted to test the influence of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposite Ratio (FDR) and Operating Expenses on Operating Income (BOPO) on Return on Assets (ROA). Data obtained from OJK publications for the period 2016-2019. Obtained 4 Sharia Banks used in this research. The analysis techniques used were multiple linear regression and hypothesis testing using tstatistics to test the coefficients of each variable and f-statis to test variable bettors together with a significance level of 5% and also perform classic assumption tests i.e. normality tests, heterocedastisity tests and multicolinearity tests. The results showed that CAR and BOPO are insignificant with significant levels above 5%, NPF is significantly negative with significant levels below 5% and positive FDR is not significant with significant levels above 5%. An F value of 0.022 indicates simultaneously having a significant influence on ROA.